Novos usos do patrimônio cultural edificado: análise da requalificação para uso cultural do Mercado Público Municipal de Jaguarão/RS - (:unkn) unknown (Universidade Federal do Pampa, 2017)
The built cultural patrimony constitutes an object of memory that keeps the history of a society. The maintenance of such spaces takes place from its use, however its poor conservation propitiates in the need of restoration what can cause in a change of uses and consequently affect the symbology of the place. The objective of this research was to analyze the uses of the Municipal Public Market of Jaguarão from its traditional forms of commerce to its new possibilities of use from the requalification project. The methodology used was qualitative research, firstly searching for information in books, scientific articles and official documents, then we conducted interviews with a representative of the current municipal management and with two traders who used the market space at the time of their interdiction. As results we can highlight: there was a change in the physical structure of the building that led to a decrease in the number of rooms; abandonment of traditional commerce with the new use of gastronomy; when privileging the tourist use of space, one loses the chance to provide the maintenance of the bond of the local community with the patrimonial asset. We conclude that, after being restored, the uses that will be attributed to the Public Market do not constitute a mediator between the patrimonial property and the community, since the new use turns to those who come from outside, the tourist, an intervention in the cultural patrimony should restore only the material aspects, but also provide a better functioning of the well as symbol.
Keywords: Patrimônio cultural edificado; Mercado Público; Requalificação urbana; Jaguarão; Cultural heritage built; Public Market; Urban requalification; Jaguarão; CNPQ::CIENCIAS HUMANAS